Deficiency of Sef Is Associated With Increased Postnatal Cortical Bone Mass by Regulating Runx2 Activity. (May 2014) - He, Qing; Yang, Xuehui; Gong, Yan; Kovalenko, Dmitry; Canalis, Ernesto; Rosen, Clifford J; Friesel, Robert E
ABSTRACT Sef (similar expression to fgf genes) is a feedback inhibitor of fibroblast growth factor (FGF) signaling and functions in part by binding to FGF receptors and inhibiting their activation. Genetic studies in mice and humans indicate an important role for fibroblast growth factor signaling in bone growth and homeostasis. We, therefore, investigated whether Sef had a function role in skeletal acquisition and remodeling. Sef expression is increased during osteoblast differentiation in vitro, and LacZ staining of Sef+/− mice showed high expression of Sef in the periosteum and chondro‐osseous junction of neonatal and adult mice. Mice with a global deletion of Sef showed increased cortical bone thickness, bone volume, and increased periosteal perimeter by micro‐computed tomography (micro‐CT). Histomorphometric analysis of cortical bone revealed a significant increase in osteoblast number. Interestingly, Sef−/− mice showed very little difference in trabecular bone by micro‐CT and histomorphometry compared with wild‐type mice. Bone marrow cells from Sef−/− mice grown in osteogenic medium showed increased proliferation and increased osteoblast differentiation compared with wild‐type bone marrow cells. Bone marrow cells from Sef−/− mice showed enhanced FGF2‐induced activation of the ERK pathway, whereas bone marrow cells from Sef transgenic mice showed decreased FGF2‐induced signaling. FGF2‐induced acetylation and stability of Runx2 was enhanced in Sef−/− bone marrow cells, whereas overexpression of Sef inhibited Runx2‐responsive luciferase reporter activity. Bone marrow from Sef−/− mice showed enhanced hematopoietic lineage‐dependent and osteoblast‐dependent osteoclastogenesis and increased bone resorptive activity relative to wild‐type controls in in vitro assays, whereas overexpression of Sef inhibited osteoclast differentiation. Taken together, these studies indicate that Sef has specific roles in osteoblast and osteoclast lineages and that its absence results in increased osteoblast and osteoclast activity with a net increase in cortical bone mass. © 2014 American Society for Bone and Mineral Research.